An Intervention in Reading Disabilities Using a Digital Tool During the COVID-19 Pandemic - Cadime, Irene; Ribeiro, Iolanda; Cruz, Joana; Cosme, Maria do Céu; Meira, Diana; Viana, Fernanda Leopoldina; Santos, Sandra (Frontiers in Psychology, 2022)
In the last decade, ICT-based interventions for developing reading skills in children with reading disabilities have become increasingly popular. This study had three goals: (a) to assess the existence of gains in word reading, oral reading fluency and listening comprehension after a Tier 2 intervention using the digital tool “I’m still learning”, which was delivered partially in a remote modality during the COVID-19 pandemic; (b) to investigate whether the gains depended on the students’ gender, the number of sessions attended and the interventionist; and (c) to investigate parents’ perceptions about the suitability and perceived effects of the intervention. A single group design with pretest and posttest was used. The intervention was delivered to second graders (N = 81) flagged as being at-risk for reading disabilities in a universal screening. The analyses showed significant gains in all three outcome variables after the intervention. The gains did not depend on students’ gender, number of intervention sessions attended or interventionist. Parents’ perceptions of the remote intervention were positive. The study findings highlight the potentialities of using technology-based interventions to foster reading skills and suggest that these may be especially useful during lockdowns.